Algorithm 728: FORTRAN subroutines for generating quadratic bilevel programming test problems - Calamai, Paul H. (1994)
This paper describes software for generating test problems for quadratic bilevel programming. The algorithm constructs problems with a number of favorable properties that can be selected and controlled by the user. The intention is to provide a set of FORTRAN 77 routines that can be used for testing, verifying, and comparing solution techniques for these problems.